Happily Ever After: A Novella Exploring the Choice between Marriage and Personal Freedom - Nathasia Jocelyn; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
In this creative thesis, I would like to explore the tension between the human needs for love/belonging and the need for personal freedom. Employing William Glasser’s Choice Theory (1998), this creative thesis portrays how societal pressures and personal histories constrain protagonists Lana and Owen, leading them to resolve their internal conflicts through conscious-intentional choices. The narrative specifically addresses why the protagonist's struggle to choose between marriage and personal freedom rooted in societal expectations and past trauma, how their views of freedom are influenced by marriage as threat to independence and a cage of responsibility, and how they navigate their choices through self-reflection, trust-building, and redefining marriage as a partnership balancing love and autonomy. Ultimately, the story demonstrates that happiness emerges from aligning personal values with relationships through open communication and deliberate decision-making. The thesis emphasizes self-awareness and intentionality in resolving internal conflicts.